ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris pada kelompok Wholesale And Retail Trade tahun 2010-2012) - Fadhli, Muhammad; -, Kamaliah; -, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to determine the factors that influence the practice of income smoothing in the company of Wholesale And Retail Trade group listed in Indonesia Stock Exchange in 2010-2012. Population that will be the object of research is the companies listed on the Stock Exchange on the Wholesale and Retail Trade group the period 2010 - 2012. Of the criteria specified then the company sampled in this study as many as 14 companies. The method used in this study is a quantitative analysis method by using statistical tools that multiple linear regression method. From the results of the research, a significant difference between the ROA, OPM on income smoothing in the Wholesale and Retail Trade. dividend payout has no effect on income smoothing in the Wholesale and Retail Trade. There is a significant relationship between managerial ownership on income smoothing in the Wholesale and Retail Trade. a significant difference between the size of the company on income smoothing in the Wholesale and Retail Trade, and no effect of dividend payout on income smoothing in the Wholesale and Retail Trade. From the results of the F test, the results of this study accepts the hypothesis that there is a significant influence between ROA, interest rates and dividend payout, financial leverage and firm size on income smoothing funds in the Wholesale and Retail Trade.Keywords: ROA, interest rates and dividend payout, financial leverage, firm size and